ASSOCIATION BETWEEN DIABETES MELLITUS TYPE II AND HELICOBACTER PYLORI INFECTION (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of H. pylori infection in patients with type II diabetes mellitus.Study Design: Cross-sectional study Place And Duration: Medicine Department of Liaquat University of Medical and Health Sciences, Jamshoro, for a duration of 6 months i.e. from Sep/2024 till Feb/2025.Patients And Methods: Based on the inclusion and exclusion criteria, 289 patients of type II diabetes mellitus were enrolled into the study. The data was recorded onto a self-structured questionnaire containing inquiries regarding basic biodata, sociodemographic details and inference obtained from a detailed clinical history of the patient, the laboratory investigation values (such as fasting blood glucose, HbAlc) was done. The Helicobacter pylori (HP) infection was diagnosed via serology and HpSA and findings were noted down and were subjected to statistical analysis.Results: The median (IQR) age of the patients was 49 (23) years. The median (IQR) duration of disease was 10 (7) years and the median (IQR) HbA1c levels were 9.7 (2.9%). There were 198 (68.5%) males and 91 (31.5%) females in the study. In terms of severity of diabetes, 44 (15.2%) patients had good diabetic control, 163 (56.4%) patients had intermediate control and 82 (28.4%) patients had poor control. HP infection was present in 124 (42.9%) patients.Conclusion: In patients with type II diabetes, H.pylori infection was present in 42.9%.